P2X7 Receptor-Dependent microRNA Expression Profile in the Brain Following Status Epilepticus in Mice - Conte, Giorgia; Nguyen, Ngoc T.; Alves, Mariana; de Diego-Garcia, Laura; Kenny, Aidan; Nicke, Annette; Henshall, David C.; Jimenez-Mateos, Eva M.; Engel, Tobias (Frontiers in Molecular Neuroscience, 2020)
The ionotropic ATP-gated P2X7 receptor is an important contributor to inflammatory signaling cascades via the release of Interleukin-1β, as well as having roles in cell death, neuronal plasticity and the release of neurotransmitters. Accordingly, there is interest in targeting the P2X7 receptor for the treatment of epilepsy. However, the signaling pathways downstream of P2X7 receptor activation remain incompletely understood. Notably, recent studies showed that P2X7 receptor expression is controlled, in part, by microRNAs (miRNAs). Here, we explored P2X7 receptor-dependent microRNA expression by comparing microRNA expression profiles of wild-type (wt) and P2X7 receptor knockout mice before and after status epilepticus. Genome-wide microRNA profiling was performed using hippocampi from wt and P2X7 receptor knockout mice following status epilepticus induced by intra-amygdala kainic acid. This revealed that the genetic deletion of the P2X7 receptor results in distinct patterns of microRNA expression. Specifically, we found that in vehicle-injected control mice, the lack of the P2X7 receptor resulted in the up-regulation of 50 microRNAs and down-regulation of 35 microRNAs. Post-status epilepticus, P2X7 receptor deficiency led to the up-regulation of 44 microRNAs while 13 microRNAs were down-regulated. Moreover, there was only limited overlap among identified P2X7 receptor-dependent microRNAs between control conditions and post-status epilepticus, suggesting that the P2X7 receptor regulates the expression of different microRNAs during normal physiology and pathology. Bioinformatic analysis revealed that genes targeted by P2X7 receptor-dependent microRNAs were particularly overrepresented in pathways involved in intracellular signaling, inflammation, and cell death; processes that have been repeatedly associated with P2X7 receptor activation. Moreover, whereas genes involved in signaling pathways and inflammation were common among up- and down-regulated P2X7 receptor-dependent microRNAs during physiological and pathological conditions, genes associated with cell death seemed to be restricted to up-regulated microRNAs during both physiological conditions and post-status epilepticus. Taken together, our results demonstrate that the P2X7 receptor impacts on the expression profile of microRNAs in the brain, thereby possibly contributing to both the maintenance of normal cellular homeostasis and pathological processes.